KARAKTERISTIK STRUKTURAL-SEMIOTIK PUISI-PUISI KARYA D. ZAWAWI IMRON - Muakibatul Hasanah (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2013)
This study aims to describe structural-semiotic characteristics of D. Zawawi Imron’s poems. This study employed a qualitative descriptive hermeneutic analysis. The findings show that D. Zawawi Imron’s poems are characterized by (1) the diction comprising the use of concrete and connotative words related to natural, social, and spiritual environments; (2) figures of speech dominated by metaphors, followed by personifications and similes; (3) descriptive, periphrastic, paradoxical, symbolic, climactic, and ironical language styles; and (4) tactile, visual, dynamic, and auditory imagery. The diction contributes to the creationof figures of speech and language styles and both contribute to the imagery creation. The semiotic characteristics are related to empirical facts as follows: (1) most poems are indices, (2) few poems are icons, and (3) no poem is a symbol. In the relationship between titles and contents of the poems, the titles serve as indices and icons for the contents, whilesymbols are only metaphorical words/phrases.